Advanced Excel reporting for management accountants - Blackwood, Neale (Hoboken, New Jersey : Wiley, 2014)
"The advanced tools accountants need to build automated, reliable, and scalable reports using ExcelLearn about the functions that work together to automate many of the processes involved in Management Reporting. See how to take advantage of the many new features of Excel 2007 and 2010. Find out how to build validation structures into your spreadsheet reports. Discover how to identify missing or new codes, either in the creation process or in the day-to-day running of the reports. Do it all with Advanced Excel Reporting for Management Accountants. Explore the structures that simplify the report creation process and make the reports more maintainable Learn techniques to "cleanse" data so that it is ready for use in Pivot Tables and formula-based reports Find out the tips and tricks that can make the creation process quicker and easier Discover all you need to know about Excel's summing functions and how versatile they can be Written in a hands-on style that works towards the completion of two reporting case studies, Advanced Excel Reporting for Management Accountants explains and demonstrates techniques so that Management Accountants can learn how to automate many aspects of the reporting process"--
Print version record and CIP data provided by publisher.
Keywords: Microsoft Excel (Computer file); Microsoft Excel (Computer file); Managerial accounting -- Computer programs; Electronic spreadsheets -- Computer programs; COMPUTERS -- Desktop Applications -- Spreadsheets; BUSINESS & ECONOMICS -- Accounting -- Managerial; Electronic spreadsheets -- Computer programs; Managerial accounting -- Computer programs; Electronic books; Electronic books